Personal monitoring of fine particulate matter (PM2.5) exposure in mothers and young children in a South African birth cohort study – A pilot study. (1st February 2023) - Vanker, Aneesa; Barnett, Whitney; Chartier, Ryan; MacGinty, Rae; Zar, Heather J.
Abstract: Air pollution is a recognized risk factor for impaired lung health and increased morbidity and mortality globally. Fine particulate matter (PM2.5 ) has been linked to respiratory illness, but assessing personal PM2.5 exposure remains difficult, especially in children. The MicroPEM™ and Enhanced Children's MicroPEM™ (ECM) are personal fine particulate matter exposure monitors that have not been well-evaluated for young children. We aimed to assess compliance and acceptability of these monitors and to investigate risk factors associated with fine particulate matter in mother-child pairs. Methods: Mother-child pairs, enrolled in a South African birth cohort, the Drakenstein Child Health Study, were recruited. A MicroPEM (mother) and ECM (child), issued to each participant and worn over 24 h, quantified PM2.5 exposure. Home environment, wearability, and wearing compliance were assessed. Linear regression identified associations between variables characterising the home environment and PM2.5 levels. Results: From August to November 2016, 86 mothers and 75 children (age 1–4 years) had results. Fossil fuels were used in 21% of homes; maternal smoking (37%) and exposure to household tobacco smoke (89%) was high. Waking wearing compliance of the devices was 59% in children and 56% in mothers. PM2.5 exposures were above the World Health Organization recommend 24-h interim target (IT-4 25 μg/m 3 ) in 38/75 (51%) children, and in 44/86 (51%) mothers. Winter, smoking and public transport were associated with higher concentrations of PM2.5 in mothers. Whereas, for the children higher concentrations of PM2.5 were associated with winter and two or more household smokers; while lower concentrations were associated with age, weight-for-age z-score and households that had fewer than two basic dimensions. Wearability for children was reported as "very easy" in the majority (n = 54, 63%) with similar acceptability in mothers (n = 55, 64%). Conclusion: The MicroPEM and ECM provide wearable low-burden personal exposure monitoring tools for women and children with reasonable rates of acceptability. High exposure to fine particulate matter in children is concerning; strategies to minimise exposure need to be strengthened. Graphical abstract: Image 1 Highlights: Personal sampling of fine particulate matter exposure is possible even in young children. The weak correlation between maternal and child PM2.5 indicates it may be important to directly measure child exposure. Acceptable compliance was found but design of device holders are important considerations for further studies. Exposures exceeded recommended PM2.5 interim targets for half of mothers and children.